Effect of AVG application on fruit set, yield and fruit size in ‘Abate Fetel’ and ‘Packam’s Triumph’ pears in a semi-commercial statistical trial - Sanchez, Enrique Eduardo; Curetti, Mariela; Retamales, Julio (ISHS, 2025)
Trabajo presentado al XI International Pear Symposium, Argentina, 2010